2019
DOI: 10.1002/ppp3.10060
|View full text |Cite
|
Sign up to set email alerts
|

The viability of a breeding programme for ash in the British Isles in the face of ash dieback

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…A further decline without joint rescue efforts at European level could cause non-reversible loss of genetic diversity which in turn could cause a critical minimum population size vital for long-term survival. Although a minor proportion of ash trees is likely inheriting resistance against ADB 32 , 33 , this alone will not guarantee that the ash population will recover after the disease has reached an equilibrium state. Evans 34 simulated that long-term recovery of ash is highly dependent on the proportion of ash trees carrying natural resistance and secondly on the degree of heritability of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A further decline without joint rescue efforts at European level could cause non-reversible loss of genetic diversity which in turn could cause a critical minimum population size vital for long-term survival. Although a minor proportion of ash trees is likely inheriting resistance against ADB 32 , 33 , this alone will not guarantee that the ash population will recover after the disease has reached an equilibrium state. Evans 34 simulated that long-term recovery of ash is highly dependent on the proportion of ash trees carrying natural resistance and secondly on the degree of heritability of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…If EAB were to arrive in the UK, it would encounter an F. excelsior population which has already been weakened by exposure to H. fraxineus. The combined effect of the two bioantagonists may prove highly destructive, at least until resistance to H. fraxineus becomes widespread (Plumb et al, 2019), at which point the partial resistance of F. excelsior to EAB may protect trees that have not been severely damaged by ash dieback.…”
Section: Discussionmentioning
confidence: 99%
“…Its populations are being severely reduced by the invasive alien fungus Hymenoscyphus fraxineus , which causes ash dieback 4 . Several previous studies have shown that there is a low frequency of heritable resistance to ADB in European ash populations 5 . Estimates of breeding values of mother trees based on observed ADB damage in their progeny have an approximately normal distribution, hinting that resistance is a polygenic trait 6 that would respond well to selection.…”
Section: Introductionmentioning
confidence: 93%